Genetic profile of the domestic pigeon Columba livia using genes associated with plumage color in Cotorra-Córdoba, Colombia (BISTUA Revista de la Facultad de Ciencias Básicas, 2022)
The objective of the research was to analyze the genetic profile of the domestic pigeon Columba livia using genes associated with plumage color in Cotorra-Córdoba, Colombia. Five subpopulations were sampled, the random samples were developed between January and February 2019, through urban excursions, direct observation and with the help of photographic records. Autosomal markers that encode plumage coloration and pattern were used: Grizzle (G); Spread (S); Checker (C) and Ash-Red (B) linked to sex. Genetic profiles were calculated with the following genetic-population indices: allelic frequencies, genetic diversity, expected heterozygosity, expected heterozygosity of the total population, genetic differentiation coefficient, gene flow, genetic distances between subpopulations, were estimated using the PopGene program. 1.31. The number of alleles per locus and Shannon's index was calculated using the FSTAT v 2.9.3.2 program. A dendrogram was drawn using the MEGA 5.2 program. The Spread and Checker loci were the ones with the highest frequencies, on the contrary Ash-red showed the lowest values, the genetic differentiation was insufficient between the subpopulations and a high gene flow, configuring the same genetic profile for this population of domestic pigeons. Possible advantages of natural selection associated with reproductive performance and physiological improvements are suggested